Implementasi Kebijakan dalam Pengelolaan Bumdes di Desa Sindang Sari Kecamatan Pabuaran, Banten - Natasya Adriani; Julia Ivanna (Departement of Mathematics Education, 2024)
This study aims to look at the implementation of policies made by the village government towards BUMDs in Sindang Sari Village, Pabuaran Subdistrict, Banten. The method used in this article uses a qualitative descriptive method, namely data collection using interview techniques and writing foundations supported by literature review in line with the discussion discussed in this article. The results show that the implementation of BUMD management policies in Sindang Sari Village still faces many challenges. Although the village government has made efforts to harmonize policies and regulations regarding BUMDs, the level of community participation is still small. This is due to the lack of a consistent and effective outreach program. Many parties are willing to join the BUMDes program either as funders or collaborators. This is due to the low level of community trust in the management of the BUMD and the lack of social support for the benefits provided by the BUMD for the welfare of the village.